Hola, guapo, ¿qué pasa? Formas de tratamiento como problema de sociopragmática intercultural y didáctica de lenguas - Baran, Marek (Neofilolog, 2023)
Recognizing that appellative systems are subjected to particular sociocultural codifications, through this study we try to verify whether the didactic presentation of the address forms, and in particular of the address forms of the Spanish-speaking world, is not limited only to a formal schematization, overlooking the interpretative clues about the scope of use and sociopragmatic conventions. Carrying out the analysis of a few manuals of Spanish as a foreign language, we try to find out what functional values acquire the address forms in the proposed contextualizations. In our approach, we take into account both pronominal and nominal address forms. Similarly, we propose to investigate the question of conceptualizations through which different methods of Spanish as a foreign language reflect the notional contents linked to the contexts of formality and proximity.